Generation of the human erythroblast-derived iPSC line UBTi001-A - Afrim Avdili; Lisa Rohrhofer; Martina Auer; Claudia Bernecker; Peter Schlenke; Isabel Dorn (Stem Cell Research, 2022)
We performed reprogramming of human erythroblasts derived from CD34+ hematopoietic stem / progenitor cells of a healthy donor. CD34+ cells were differentiated in-vitro into a pure population of CD36+ erythroblasts and nucleofected with four episomal plasmids expressing SOX2, OCT3/4, KLF4, LIN28, L-MYC and TP53-shRNA. The established iPSC line showed normal karyotype. Pluripotency was confirmed by expression of pluripotency markers and in-vitro differentiation into tissues of all three germ layers. The UBTi001-A iPSC line might provide an attractive source for developmental research on human hematopoiesis and erythropoiesis.